1993
DOI: 10.5014/ajot.47.4.311
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rater Severity On Person Ability Measure: A Rasch Model Analysis

Abstract: This paper presents a method for analyzing oral examinations with an extended, many-faceted Rasch model that calibrates medical specialty candidates, protocols, and raters. Significant variance was found among protocol difficulties and rater severities. When candidates' raw scores were compared with calibrated measures corrected for the bias caused by the particular protocols and raters encountered, variation between candidate scores and measures were observed. The data were found to fit the Rasch model well e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…It might also be of interest to consider whether the AHA could be extended to be suitable for older age groups by adding more challenging and age-appropriate tasks. A further area of future investigation is to determine whether the influence of differences of leniency of the raters affects the precision of the measures [42,43]. The instrument's responsiveness to changes in performance abilities seems promising, according to preliminary data from an ongoing intervention study, and is a very important issue for further investigation since we urgently need sensitive tools to evaluate the effectiveness of treatment in paediatric rehabilitation.…”
Section: The Test Constructmentioning
confidence: 99%
“…It might also be of interest to consider whether the AHA could be extended to be suitable for older age groups by adding more challenging and age-appropriate tasks. A further area of future investigation is to determine whether the influence of differences of leniency of the raters affects the precision of the measures [42,43]. The instrument's responsiveness to changes in performance abilities seems promising, according to preliminary data from an ongoing intervention study, and is a very important issue for further investigation since we urgently need sensitive tools to evaluate the effectiveness of treatment in paediatric rehabilitation.…”
Section: The Test Constructmentioning
confidence: 99%
“…In several studies (18,19) the variability between raters in terms of severity or leniency has been demonstrated. Raters seem to establish an individual profile of severity and usually tend to maintain this across clients and protocols (18).…”
Section: Discussionmentioning
confidence: 99%
“…Raters seem to establish an individual profile of severity and usually tend to maintain this across clients and protocols (18). The results from this study, with rater severity varying, in session 1 from (/0.51 (lenient) to 0.27 (severe) logits, and in session 2 from (/0.37 to 0.28 logits (Table II), and with a calibration difference of less than 0.16 logits, are in line with those findings.…”
Section: Discussionmentioning
confidence: 99%
“…1 The many-facet Rasch model (MFRM) has been successfully used to adjust for rater stringency/leniency effects on candidate scores from orals and essays. [2][3][4][5] It has been suggested that the MFRM might be successfully applied to large-scale, high-stakes OSCEs. 6,7 It appears that the MFRM might be a useful tool for those engaged in OSCEs and assessments using rating systems where all candidates/students are not rated by the same rater(s).…”
mentioning
confidence: 99%
“…Inconsistency of raters on oral examinations has been studied extensively. 2,10,[18][19][20][21][22] In 1993, Lunz and Stahl 10 reviewed an oral examination administered by the American Board of Urology. They found that examinees with identical raw scores often had differing ability measures after removing the effects because of rater stringency/leniency and case difficulty.…”
mentioning
confidence: 99%